Curing accelerator, preparation method of curing accelerator, cofferdam glue and application of cofferdam glue
By using curing accelerators with silicon-oxy-silicon skeletons and imidazole groups in cofferdams, the problems of poor reliability and insufficient curing characteristics of cofferdams in high-temperature reflux support chip devices are solved, and the effects of improving toughness, crack resistance and storage stability are achieved.
Patent Information
- Application Number
- CN202411953375.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing cofferdam glue has poor reliability in chip devices supported by high temperature reflux, and has high curing temperature, insufficient toughness and storage stability, making it difficult to meet the strict reliability requirements.
A curing accelerator is used, and its structure includes silicone flexible segments and imidazole groups with silicon-oxy-silica as the skeleton, and is prepared by hydrolysis and condensation reaction of silane coupling agent to improve the toughness and compatibility of cofferdams.
It improves the toughness and crack resistance of cofferdams, enhances its reliability, and significantly reduces the reactivity of imidazole groups, improves storage stability and long-term operational properties.
Smart Images

Figure CN119859270A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of adhesives, and in particular to a curing accelerator and a preparation method thereof, a cofferdam adhesive and an application thereof. Background Art
[0002] The dam glue has excellent sealing and corrosion resistance, and is widely used in technical fields such as electronic packaging. According to different curing methods, the dam glue is mainly divided into UV curing dam glue and thermal curing dam glue. Among them, UV curing dam glue has the characteristics of fast curing rate and high degree of automation, but its product has a low glass transition temperature and poor reliability, and it is difficult to match chip devices with high temperature reflow support. Thermal curing dam glue has the advantages of high glass transition temperature and high reliability, but single-component dam glue generally requires low temperature storage, poor long-term operation stability, and the curing temperature is usually above 150°C, with poor curing stress and poor toughness.
[0003] In the related art, rubber or block copolymers are generally added to disperse stress, thereby improving the toughness of the cofferdam glue. However, the addition of high molecular weight toughening agents will lead to compatibility problems and cannot meet the application requirements of the cofferdam glue under strict reliability. Summary of the invention
[0004] The embodiments of the present application provide a curing accelerator and a preparation method thereof, a cofferdam glue and an application thereof. The curing accelerator is applied to the cofferdam glue to improve toughness while ensuring good compatibility, thereby improving the reliability of the cofferdam glue.
[0005] In a first aspect, the embodiments of the present application provide a curing accelerator, the structural formula of the curing accelerator is shown in Formula I:
[0006]
[0007] Wherein, R1 and R2 are independently selected from any one of hydrogen, substituted or unsubstituted alkyl, substituted or unsubstituted phenyl, substituted or unsubstituted propenyl, substituted or unsubstituted epoxy; R3-R5 are independently selected from any one of hydrogen, substituted or unsubstituted alkyl and substituted or unsubstituted phenyl;
[0008] The value range of x is 1-100, the value range of y is 1-100, and the value range of n is 1-5.
[0009] Optionally, the value range of x is 1-10, and the value range of y is 1-10.
[0010] In a second aspect, an embodiment of the present application provides a method for preparing a curing accelerator, which is used to prepare the curing accelerator as described above, comprising:
[0011] Dispersing a silane coupling agent into a first solvent to hydrolyze the silane coupling agent to obtain a first solution; wherein the silane coupling agent has an imidazole group;
[0012] Dissolving hydroxy silicone oil in a second solvent to obtain a second solution, adding the first solution and a surfactant to the second solution, allowing the hydrolyzed silane coupling agent to undergo a condensation reaction with the hydroxy silicone oil to obtain a reaction solution;
[0013] The solvent in the reaction solution is removed and dried to obtain a curing accelerator.
[0014] Optionally, dispersing the silane coupling agent into the first solvent to hydrolyze the silane coupling agent comprises:
[0015] Disperse the silane coupling agent in anhydrous ethanol, adjust the pH to alkaline, add deionized water at a temperature of 40°C-50°C, and maintain for 2h-3h to hydrolyze the silane coupling agent.
[0016] Optionally, dissolving the hydroxy silicone oil in a second solvent to obtain a second solution, adding the first solution and a surfactant to the second solution, and causing the hydrolyzed silane coupling agent to undergo a condensation reaction with the hydroxy silicone oil, comprising:
[0017] Dissolving hydroxy silicone oil in anhydrous ethanol and adjusting the pH to alkaline to obtain a second solution;
[0018] Add the surfactant and the first solution to the second solution, and react at a temperature of 40° C. to 50° C. for 6 h to 10 h to allow the hydrolyzed silane coupling agent to undergo a condensation reaction with the hydroxy silicone oil.
[0019] Optionally, removing the solvent from the reaction solution, after drying, comprises:
[0020] The reaction solution was distilled under reduced pressure to remove the solvent in the reaction solvent, and then vacuum dried.
[0021] In a third aspect, an embodiment of the present application provides a cofferdam glue, comprising the following components in parts by weight: 5-15 parts of epoxy resin, 60-80 parts of filler, 10-15 parts of curing agent, 1-10 parts of curing accelerator, 1-5 parts of thixotropic agent and 0.5-3 parts of coupling agent;
[0022] Wherein, the curing accelerator includes the curing accelerator as described above, and / or the curing accelerator prepared by the preparation method of the curing accelerator as described above.
[0023] Optionally, the epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, naphthalene epoxy resin, aminophenol epoxy resin, aliphatic epoxy resin and biphenyl epoxy resin;
[0024] and / or, the molecular weight of the epoxy resin is less than or equal to 600;
[0025] And / or, the filler comprises spherical silica, the particle size of the spherical silica is distributed in the range of 1 μm-100 μm, and the average particle size is 5 μm-20 μm;
[0026] and / or, the curing agent comprises at least one of an amine curing agent and an acid anhydride curing agent;
[0027] and / or, the coupling agent includes at least one of an epoxy coupling agent, an amino coupling agent, an aniline coupling agent, a mercapto coupling agent and a vinyl coupling agent;
[0028] And / or, the thixotropic agent includes at least one of fumed silica, organic bentonite and hydrogenated castor oil.
[0029] Optionally, the curing agent includes an anhydride curing agent, and the molecular weight of the anhydride curing agent is less than or equal to 500.
[0030] In a fourth aspect, embodiments of the present application provide application of the dam glue as described above in electronic device packaging.
[0031] Beneficial effects of the embodiments of the present application:
[0032] In an embodiment of the present application, a curing accelerator is provided, which is applied to cofferdam glue. The structural formula of the curing accelerator is shown in Formula I. Since the curing accelerator has a flexible silicone segment with a silicon-oxygen-silicon skeleton, the molecular structure of the curing accelerator can achieve a certain degree of freedom, and the flexible silicone segment has good compatibility with materials such as resin in the cofferdam glue. When applied to the cofferdam glue, it can improve the toughness of the cofferdam glue and improve the crack resistance, thereby ensuring the reliability of the cofferdam glue. In addition, in the curing accelerator, the reaction activity of the imidazole group can be significantly reduced by grafting the flexible silicone segment with the imidazole group. After being applied to the cofferdam glue, it can improve the storage stability of the cofferdam glue and ensure the long-term operability of the cofferdam glue. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 It is a comparison chart of the aspect ratios of the cofferdam glue in Example 1 and Comparative Example 1 under different conditions. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0036] In a first aspect, an embodiment of the present application provides a curing accelerator, which is applied to cofferdam glue. The structural formula of the curing accelerator is shown in Formula I:
[0037]
[0038] Wherein, R1 and R2 are independently selected from any one of hydrogen, substituted or unsubstituted alkyl, substituted or unsubstituted phenyl, substituted or unsubstituted propenyl, substituted or unsubstituted epoxy; R3-R5 are independently selected from any one of hydrogen, substituted or unsubstituted alkyl and substituted or unsubstituted phenyl;
[0039] The value range of x is 1-100, the value range of y is 1-100, and the value range of n is 1-5.
[0040] A curing accelerator provided in an embodiment of the present application is applied to cofferdam glue. The structural formula of the curing accelerator is shown in Formula I. Since the curing accelerator contains a flexible silicone segment with a silicon-oxygen-silicon skeleton, the molecular structure of the curing accelerator can achieve a certain degree of freedom, and the flexible silicone segment has good compatibility with materials such as the resin in the cofferdam glue. When applied to the cofferdam glue, it can improve the toughness of the cofferdam glue and improve the crack resistance, thereby ensuring the reliability of the cofferdam glue. In addition, in the curing accelerator, the reaction activity of the imidazole group can be significantly reduced by grafting the flexible silicone segment with the imidazole group. After being applied to the cofferdam glue, it can improve the storage stability of the cofferdam glue and ensure the long-term operability of the cofferdam glue.
[0041] Wherein, when R1 and R2 are any one of substituted or substituted alkyl, substituted or unsubstituted phenyl, substituted or unsubstituted propenyl, and substituted or unsubstituted epoxy, the number of carbon atoms is preferably 1 to 6. When R3-R5 are any one of substituted or unsubstituted alkyl and substituted or unsubstituted phenyl, the number of carbon atoms is preferably 1 to 6.
[0042] In some embodiments, the value range of x is 1-10, and the value range of y is 1-10.
[0043] In some embodiments, n=2. That is, three alkylene groups are arranged between the imidazole group and the organic silicon flexible chain segment, so that the organic silicon flexible chain segment has a certain degree of freedom.
[0044] In a second aspect, an embodiment of the present application provides a method for preparing a curing accelerator, which is used to prepare the curing accelerator as described above, comprising:
[0045] Dispersing a silane coupling agent into a first solvent to hydrolyze the silane coupling agent to obtain a first solution; wherein the silane coupling agent has an imidazole group;
[0046] Dissolving hydroxy silicone oil in a second solvent to obtain a second solution, adding the first solution and a surfactant to the second solution, allowing the hydrolyzed silane coupling agent to undergo a condensation reaction with the hydroxy silicone oil to obtain a reaction solution;
[0047] The solvent in the reaction solution is removed and dried to obtain a curing accelerator.
[0048] In the preparation method of the curing accelerator provided in the embodiment of the present application, after the silane coupling agent is hydrolyzed, hydroxy silane and the corresponding alcohol can be formed. Hydroxy silane has active hydroxyl groups and can undergo condensation reaction with the hydroxyl groups in hydroxy silicone oil to form a flexible silicone segment. Since the silane coupling agent has an imidazole group, the flexible silicone segment can be grafted with an imidazole group. The imidazole group has a curing-promoting effect. Since it is grafted on the flexible silicone segment, the reactivity of the imidazole group can be significantly reduced. When applied to the cofferdam glue, it can improve the storage stability of the cofferdam glue and ensure the long-term operability of the cofferdam glue.
[0049] Illustratively, the synthesis path of the curing accelerator provided in the embodiments of the present application is shown in Formula II:
[0050]
[0051] In some embodiments, dispersing the silane coupling agent into a first solvent to hydrolyze the silane coupling agent comprises:
[0052] Disperse the silane coupling agent in anhydrous ethanol, adjust the pH to alkaline, add deionized water at a temperature of 40°C-50°C, and maintain for 2h-3h to hydrolyze the silane coupling agent.
[0053] Using anhydrous ethanol as the first solvent facilitates the removal of the first solvent from the solution in the later stage and is easy to recycle. Under alkaline conditions, the hydrolysis reaction of the silane coupling agent is more rapid, shortening the time required for hydrolysis. The temperature is set at 40°C-50°C, which can ensure the stability of the hydrolysis reaction, improve the efficiency of the hydrolysis reaction, and reduce side reactions.
[0054] In the hydrolysis process, continuous stirring at a speed of 300r / min-400r / min can ensure that the silane coupling agent is fully in contact with water during the hydrolysis reaction, which helps to form a more stable and uniform hydrolysis product. Deionized water can be added by dropwise addition to ensure reaction stability, and the dropwise addition speed can be controlled according to the reaction situation.
[0055] The pH value can be adjusted to about 7.5, which can reduce the occurrence of side reactions such as polycondensation while ensuring the hydrolysis efficiency and hydrolysis stability.
[0056] In some embodiments, hydroxy silicone oil is dissolved in a second solvent to obtain a second solution, and the first solution and a surfactant are added to the second solution, and the reaction comprises:
[0057] Dissolving hydroxy silicone oil in anhydrous ethanol and adjusting the pH to alkaline to obtain a second solution;
[0058] Add the surfactant and the first solution to the second solution, and react at a temperature of 40° C. to 50° C. for 6 h to 10 h to allow the hydrolyzed silane coupling agent to undergo a condensation reaction with the hydroxy silicone oil.
[0059] The second solvent also uses anhydrous ethanol, which is convenient for removing the second solvent from the solution later and is easy to recycle. When reacting under alkaline conditions, water molecules easily lose protons to form hydroxide ions. These hydroxide ions can attack the silicon-oxygen bonds in the hydrolyzate of the silane coupling agent in the first solution, thereby improving the efficiency of the condensation reaction and ensuring the stability of the reaction. By adding a surfactant, the dispersibility and stability can be improved, the agglomeration and sedimentation phenomena can be reduced, and the reaction can be carried out stably. The surfactant can accelerate the contact and mixing between the components, thereby promoting the reaction. Carrying out the reaction at a temperature of 40°C-50°C can balance the reaction stability and reaction rate. By reacting for 6h-10h, it can ensure that the reaction is sufficient and balance the product yield and production cost.
[0060] In some embodiments, removing the solvent from the reaction solution, after drying, comprises:
[0061] The reaction solution was distilled under reduced pressure to remove the solvent in the reaction solvent, and then vacuum dried.
[0062] Vacuum distillation can reduce the boiling point of the solvent, reduce the problem of product decomposition or deterioration caused by high temperature, and improve separation efficiency. Vacuum drying is more efficient and can be dried at a lower temperature to ensure the stability of the product.
[0063] Exemplarily, the reduced pressure distillation is carried out at room temperature, and the pressure during the reduced pressure distillation is controlled at 1.5 kPa.
[0064] In some embodiments, the silane coupling agent includes at least one of N-(trimethoxysilylpropyl)imidazole and N-[3-(triethoxysilyl)propyl]-4,5-dihydroimidazole.
[0065] In some embodiments, the hydroxy silicone oil includes at least one of silanol-terminated polydimethylsiloxane and hydroxy-terminated phenyl silicone oil.
[0066] In a third aspect, an embodiment of the present application provides a cofferdam glue, comprising the following components by weight: 5-15 parts of epoxy resin, 60-80 parts of filler, 10-15 parts of curing agent, 1-10 parts of curing accelerator, 1-5 parts of thixotropic agent and 0.5-3 parts of coupling agent. The curing accelerator comprises the curing accelerator as described above, and / or the curing accelerator prepared by the preparation method of the curing accelerator as described above.
[0067] The cofferdam glue provided in the embodiment of the present application includes the curing accelerator as described above. Since the curing accelerator contains a flexible silicone segment with a silicon-oxygen-silicon skeleton, the molecular structure of the curing accelerator can achieve a certain degree of freedom, and the flexible silicone segment has good compatibility with materials such as the resin in the cofferdam glue, which can improve the toughness of the cofferdam glue and improve the crack resistance, thereby ensuring the reliability of the cofferdam glue. In addition, the curing accelerator is grafted with an imidazole group by the flexible silicone segment, which can significantly reduce the reactivity of the imidazole group, improve the storage stability of the cofferdam glue, and ensure the long-term operability of the cofferdam glue. That is, the cofferdam glue provided in the embodiment of the present application has high latency and strong toughness.
[0068] Epoxy resin has good adhesion, corrosion resistance and mechanical strength, which can ensure that the cofferdam glue has excellent physical and chemical properties. Fillers can increase, reduce costs and adjust performance. A higher filler ratio can improve the hardness and wear resistance of the cofferdam glue while reducing costs. Curing agents can make the cofferdam glue solidify under appropriate conditions. Thixotropic agents can improve the rheological properties of the cofferdam glue, making it have a higher viscosity in the vertical direction, keep its shape during application, and not easy to flow.
[0069] In some embodiments, the epoxy resin includes at least one of bisphenol A type epoxy resin, bisphenol F type epoxy resin, naphthalene type epoxy resin, aminophenol type epoxy resin, aliphatic epoxy resin, and biphenyl epoxy resin.
[0070] Bisphenol A epoxy resin has excellent bonding properties and chemical corrosion resistance, which can ensure the bonding properties and corrosion resistance of the cofferdam glue. Bisphenol F epoxy resin has good weather resistance and thermal stability, which helps to improve the weather resistance and thermal stability of the cofferdam glue. Naphthalene epoxy resin has good high temperature resistance and mechanical strength, which improves the high temperature resistance of the cofferdam glue, and improves the tensile strength and tear strength. Aminophenol epoxy resin has good processing properties and flexibility. Aliphatic epoxy resin has a lower cost, releases less volatile organic compounds during the curing process, and has better environmental protection. Biphenyl epoxy resin has excellent electrical insulation and arc melting properties, which can improve the insulation properties of the cofferdam glue.
[0071] The cofferdam glue provided in the embodiment of the present application can be selected from one or more of the above-mentioned epoxy resins as needed.
[0072] Among them, the epoxy resin can preferably be biphenyl epoxy resin or aliphatic epoxy resin with strong heat resistance to improve the high temperature resistance of the cofferdam glue.
[0073] In some embodiments, the molecular weight of the epoxy resin is less than or equal to 600. Low molecular weight epoxy resin has better permeability and fluidity. By making the molecular weight of the epoxy resin added in the cofferdam glue less than or equal to 600, the epoxy resin can be more fully penetrated into various gaps and pores, ensuring close contact and firm bonding between the cofferdam glue and the substrate. At the same time, good fluidity can also make the cofferdam glue easier to apply and spread during construction, improving construction efficiency and quality. Low molecular weight epoxy resin also has a faster curing speed, which helps to reduce shrinkage and deformation during the curing process, and ensure the flatness and stability of the cofferdam glue. In addition, low molecular weight epoxy resin is also helpful to improve the flexibility and elasticity of the cofferdam glue, and the cost of low molecular weight epoxy resin is relatively low.
[0074] In some embodiments, the filler includes spherical silica, and the particle size of the spherical silica is distributed in the range of 1 μm to 100 μm, with an average particle size of 5 μm to 20 μm.
[0075] Spherical silica has high hardness and strength, which can improve the hardness and wear resistance of the cofferdam glue. The particle size of spherical silica is distributed in 1μm-100μm, which helps to evenly disperse the spherical silica in the cofferdam glue, forming an effective reinforcement phase and improving the overall strength of the cofferdam glue. Spherical silica with an average particle size of 5μm-20μm can enhance the tear resistance of the cofferdam glue. When the cofferdam glue is torn by external force, the spherical silica particles can be fixed in the colloid like an "anchor point", thereby preventing the expansion of the tear.
[0076] In addition, spherical silica is a chemically stable inorganic material that can improve the corrosion resistance of the cofferdam glue. Spherical silica also has a high melting point, which can improve the heat resistance of the cofferdam glue.
[0077] Among them, spherical silica can also be selected to be grafted modified silica. According to the application scenarios and needs of the cofferdam glue, the spherical silica can be grafted and modified to improve the performance of the cofferdam glue.
[0078] In some embodiments, the curing agent includes at least one of an amine curing agent and an acid anhydride curing agent. Among them, the amine curing agent can react with the epoxy group through the amino group to change the polarity of the system to achieve curing. The acid anhydride curing agent can react with the epoxy group through the acid group in the acid anhydride to generate an ester structure, thereby forming a three-dimensional cross-linked structure to achieve a curing effect.
[0079] In some embodiments, the curing agent is an anhydride curing agent, and the molecular weight of the anhydride curing agent is less than or equal to 500. The product cured by the anhydride curing agent has high heat resistance and chemical corrosion resistance, which helps to maintain stability under high temperature and chemical corrosion conditions, and no volatile organic compounds are produced during the curing reaction, which is environmentally friendly. The anhydride curing agent with a molecular weight less than or equal to 500 has good weather resistance and stability, which helps to ensure the stability and durability of the cofferdam glue. And the low molecular weight anhydride curing agent has low volatility, which helps to reduce harmful gas emissions during the curing process.
[0080] In some embodiments, the anhydride curing agent includes at least one of an aromatic anhydride curing agent, an alicyclic anhydride curing agent, a long-chain aliphatic anhydride curing agent, and an anhydride adduct curing agent.
[0081] Among them, alicyclic acid anhydride curing agents are preferred. The molecular structure of alicyclic acid anhydride curing agents does not contain benzene rings, so they have good weather resistance, and the product cured by alicyclic acid anhydride curing agents has good flexibility and heat resistance.
[0082] In some embodiments, the coupling agent includes at least one of an epoxy coupling agent, an amino coupling agent, an aniline coupling agent, a thiol coupling agent, and a vinyl coupling agent.
[0083] The main function of coupling agent in cofferdam glue is to enhance the adhesion and compatibility between materials, thereby improving the overall performance of cofferdam glue.
[0084] In some embodiments, the coupling agent includes an epoxy coupling agent. The epoxy coupling agent has an epoxy group, which can react with functional groups such as hydroxyl and carboxyl in the resin to form a chemical bond, which can improve the adhesion and heat resistance of the cofferdam glue, thereby improving the stability of the cofferdam glue. The epoxy coupling agent has good compatibility with the cofferdam glue of the epoxy resin system, and can react with the hydroxyl group on the surface of silica to improve the wet heat performance of the cofferdam glue.
[0085] In addition, the coupling agent may also be a methylsilane coupling agent.
[0086] In some embodiments, the thixotropic agent includes at least one of fumed silica, organobentonite, and hydrogenated castor oil.
[0087] Among them, fumed silica has high surface activity and a large number of silanol groups on the surface, which can be connected together through hydrogen bonds to form a silica network and produce thixotropic properties. After being applied to the cofferdam glue, fumed silica can improve the thixotropy of the rubber, making the rubber easy to flow when it receives shear force, and restore viscosity after the shear force disappears, maintaining a stable shape. Organic bentonite has good thickening, thixotropy and suspension stability, and can improve the viscosity and thixotropy of the cofferdam glue. The molecules of hydrogenated castor oil have a long-chain fatty acid structure, which changes its viscosity under the action of shear force and exhibits good thixotropic properties. At the same time, hydrogenated castor oil can also improve the lubricity and wear resistance of the cofferdam glue.
[0088] In some embodiments, the thixotropic agent is preferably fumed silica and / or organic bentonite, which helps to ensure high thixotropic and high-aspect ratio characteristics of the cofferdam glue.
[0089] In a fourth aspect, embodiments of the present application provide application of the dam glue as described above in electronic device packaging.
[0090] By applying the above-mentioned cofferdam glue to electronic device packaging, good flexibility and latency can be ensured, and the packaging effect can be ensured while improving stability and reliability. Especially for high-end chip packaging, by applying the cofferdam glue provided in the embodiment of the present application, excellent stability and reliability can be ensured.
[0091] The following examples are further described in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually based on the conditions recommended by the manufacturer.
[0092] It should be noted that in the following examples and comparative examples, unless otherwise specified, all parts are by mass.
[0093] Example 1
[0094] (1) fully dispersing 50 parts of N-(trimethoxysilylpropyl)imidazole in anhydrous ethanol, starting stirring, controlling the stirring speed at 300 r / min, adjusting the pH value to 8, slowly adding deionized water, and continuously stirring at a temperature of 40° C. for 2 h to fully hydrolyze N-(trimethoxysilylpropyl)imidazole to obtain a first solution;
[0095] (2) dissolving 40 parts of low molecular weight silanol-terminated polydimethylsiloxane (product number: Dow Corning PMX-0156) in anhydrous ethanol, adjusting the pH to 8, adding the phase transfer catalyst tetrabutylammonium bromide and the first solution while stirring, and stirring the reaction at a temperature of 40° C. for 8 hours to obtain a reaction solution;
[0096] (3) performing reduced pressure distillation on the reaction solution at room temperature to remove the solvent, and obtaining a curing accelerator after vacuum drying; wherein the pressure during the reduced pressure distillation is set to 1.5 kPa;
[0097] (4) 6 parts of bisphenol F epoxy resin, 5 parts of biphenyl epoxy resin, 12 parts of phthalic anhydride, 0.5 parts of γ-glycidyloxypropyl trimethoxysilane coupling agent, 1 part of fumed silica and 2 parts of organic bentonite were sequentially added into a reaction kettle and mixed evenly, and stirred for 1 hour to obtain a first mixture;
[0098] (5) Add 70 parts of spherical silica filler to the first mixture in four batches, stir and disperse for 1 hour, then add 2 parts of the curing accelerator prepared in step (3), stir for 0.5 hour, and obtain the cofferdam glue.
[0099] Example 2
[0100] The difference between this embodiment and embodiment 1 is that:
[0101] Step (4), 6 parts of bisphenol F epoxy resin, 5 parts of biphenyl epoxy resin, 12 parts of phthalic anhydride, 0.5 parts of γ-glycidyloxypropyl trimethoxysilane coupling agent, 1 part of fumed silica and 2 parts of organic bentonite are sequentially added into a reaction kettle, mixed evenly, and stirred for 1 hour to obtain a first mixture;
[0102] The remaining conditions remain the same as those in Example 1.
[0103] Example 3
[0104] (1) 50 parts of N-[3-(triethoxysilyl)propyl]-4,5-dihydroimidazole were fully dispersed in anhydrous ethanol, stirring was started, the stirring speed was controlled at 400 r / min, the pH value was adjusted to 8, deionized water was slowly added dropwise, and stirring was continued for 3 hours at a temperature of 40° C. to fully hydrolyze N-[3-(triethoxysilyl)propyl]-4,5-dihydroimidazole to obtain a first solution;
[0105] (2) dissolving 40 parts of hydroxyl-terminated phenyl silicone oil in anhydrous ethanol, adjusting the pH to 8, adding the phase transfer catalyst tetrabutylammonium bromide and the first solution while stirring, and continuously stirring the reaction at a temperature of 40° C. for 8 hours to obtain a reaction solution;
[0106] (3) performing reduced pressure distillation on the reaction solution at room temperature to remove the solvent, and obtaining a curing accelerator after vacuum drying; wherein the pressure during the reduced pressure distillation is set to 1.5 kPa;
[0107] (4) 6 parts of bisphenol F epoxy resin, 5 parts of biphenyl epoxy resin, 12 parts of phthalic anhydride, 0.5 parts of γ-glycidyloxypropyl trimethoxysilane coupling agent, 1 part of fumed silica and 2 parts of organic bentonite were sequentially added into a reaction kettle and mixed evenly, and stirred for 1 hour to obtain a first mixture;
[0108] (5) Add 70 parts of spherical silica filler to the first mixture in four batches, stir and disperse for 1 hour, then add 2 parts of the curing accelerator prepared in step (3), stir for 0.5 hour, and obtain the cofferdam glue.
[0109] Comparative Example 1
[0110] (1) 6 parts of bisphenol F epoxy resin, 5 parts of biphenyl epoxy resin, 12 parts of phthalic anhydride, 0.5 parts of γ-glycidyloxypropyl trimethoxysilane coupling agent, 1 part of fumed silica and 2 parts of organic bentonite were added to a reaction kettle in sequence, mixed evenly, and stirred for 1 hour to obtain a first mixture;
[0111] (2) 70 parts of spherical silica filler were added to the first mixture in four batches, stirred and dispersed for 1 hour, and then 2 parts of 2-methylimidazole were added.
[0112] Comparative Example 2
[0113] (1) 6 parts of bisphenol F epoxy resin, 5 parts of biphenyl epoxy resin, 12 parts of phthalic anhydride, 0.5 parts of γ-glycidyloxypropyl trimethoxysilane coupling agent, 1 part by mass of fumed silica and 2 parts of organic bentonite were sequentially added into a reaction kettle and mixed evenly, and stirred for 1 hour to obtain a first mixture;
[0114] (2) 70 parts of spherical silica filler were added to the first mixture in four batches, stirred and dispersed for 1 hour, and then 2 parts of imidazole shell warping accelerator (HX-3722 from Asahi Kasei Corporation) were added.
[0115] The performance of the cofferdam glue in Examples 1-3 and Comparative Examples 1-2 was tested, wherein the test indicators and methods included:
[0116] (1) Viscosity measurement: The room temperature viscosity of the cofferdam glue at T0 (initial state) and T3 (three days at room temperature) was tested using a DV2T HB viscometer with the temperature controlled at room temperature and the speed of 5 rpm. The viscosity value was obtained after 60 seconds of reading.
[0117] (2) Aspect ratio measurement: Test the aspect ratio of the dam glue at T0 (initial state) and T1 (one day at room temperature); use a screw valve to dispense glue, use a printed circuit board as the substrate, do not set the valve temperature, perform three U-shaped dam operations, and measure the aspect ratio;
[0118] (3) Differential scanning calorimetry: The test was conducted using a TA instrument with the program set to heat from 30°C to 300°C, a heating rate of 10°C / min, air atmosphere, and the starting reaction temperature and peak temperature were measured;
[0119] (4) Bending test: The glue was solidified into a block, and then polished into a long block with a width and thickness of 80 mm*10 mm*4.0 mm. A universal testing machine was used for bending test at a test rate of 5 mm / min.
[0120] (5) Determination of elongation at break: The glue was cured into dumbbell-shaped specimens and stretched using a universal testing machine at a stretching rate of 5 mm / min;
[0121] (6) High and low temperature cycle: The chip device is protected by a dam glue, and the device is packaged and cured; the device is pre-conditioned according to the MSL3 of the JEDES-STD-22 standard, and the pre-treatment condition is a constant temperature of 125°C for 24 hours, and the aging box absorbs moisture for 168 hours at 85°C and 60% RH. Then it is subjected to three reflow high temperature treatments. The reflow oven program is set to ensure that the device is heated at a temperature above 220°C for 300 seconds; after pre-treatment, the device is placed in an environmental test equipment temperature cycle test box for a -55°C-125°C TCT cycle, with a cycle period of 700. A microscope is used to observe whether there are cracks in the dam glue body around the device, and the number of cracks is used for evaluation.
[0122] The test results are shown in Table 1 and Figure 1 As shown:
[0123] Table 1 Performance parameters and reliability results of Examples 1-3 and Comparative Examples 1-2
[0124]
[0125] As shown in Table 1 and Figure 1As shown, through Examples 1-3 and Comparative Example 1, it can be found that the addition of the curing accelerator provided in the examples of the present application significantly prolongs the room temperature stability of the cofferdam glue, significantly weakens the reaction activity, stabilizes the aspect ratio without collapse, obtains good latent effect and shape retention ability, and can match long-cycle assembly line operations. Compared with Comparative Example 2, the bending modulus and elongation at break of Examples 1-3 are significantly increased, and the cofferdam glue has excellent toughness.
[0126] It can be seen from the reliability results in Table 1 that by adopting the curing accelerator provided in the embodiment of the present application and introducing the flexible silicone flexible chain segment into the cofferdam glue, it is possible to effectively resist the generation of body cracks, release internal stress, and have good reliability.
[0127] In summary, after the curing accelerator provided in the present application is applied to the cofferdam glue, the cofferdam glue has high reliability and long-term storage stability, and will have broad application value and development prospects in the field of electronic device packaging.
[0128] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A curing accelerator, characterized in that: The structural formula of the curing accelerator is shown in Formula I: Wherein, R1 and R2 are independently selected from any one of hydrogen, substituted or unsubstituted alkyl, substituted or unsubstituted phenyl, substituted or unsubstituted propenyl, substituted or unsubstituted epoxy; R3-R5 are independently selected from any one of hydrogen, substituted or unsubstituted alkyl and substituted or unsubstituted phenyl; The value range of x is 1-100, the value range of y is 1-100, and the value range of n is 1-5.
2. The curing accelerator according to claim 1, characterized in that The value range of x is 1-10, and the value range of y is 1-10.
3. A method for preparing a curing accelerator, for preparing the curing accelerator according to claim 1 or 2, characterized in that: include: Dispersing a silane coupling agent into a first solvent to hydrolyze the silane coupling agent to obtain a first solution; wherein the silane coupling agent has an imidazole group; dissolving hydroxy silicone oil in a second solvent to obtain a second solution, adding the first solution and a surfactant to the second solution, allowing the hydrolyzed silane coupling agent to undergo a condensation reaction with the hydroxy silicone oil to obtain a reaction solution; The solvent in the reaction solution is removed and dried to obtain the curing accelerator.
4. The method for preparing a curing accelerator according to claim 3, characterized in that: The step of dispersing the silane coupling agent into the first solvent to hydrolyze the silane coupling agent comprises: The silane coupling agent is dispersed in anhydrous ethanol, the pH is adjusted to alkaline, deionized water is added at a temperature of 40° C.-50° C., and maintained for 2 h-3 h to hydrolyze the silane coupling agent.
5. The method for preparing a curing accelerator according to claim 3, characterized in that: The step of dissolving the hydroxy silicone oil in a second solvent to obtain a second solution, adding the first solution and a surfactant to the second solution, and causing the hydrolyzed silane coupling agent to undergo a condensation reaction with the hydroxy silicone oil comprises: Dissolving the hydroxy silicone oil in anhydrous ethanol and adjusting the pH to alkaline to obtain the second solution; The surfactant and the first solution are added to the second solution, and the mixture is reacted at a temperature of 40° C. to 50° C. for 6 h to 10 h, so that the hydrolyzed silane coupling agent undergoes a condensation reaction with the hydroxy silicone oil.
6. The method for preparing a curing accelerator according to claim 3, characterized in that: The removing of the solvent from the reaction solution, after drying, comprises: The reaction solution is subjected to reduced pressure distillation to remove the solvent in the reaction solvent, and then vacuum drying is performed.
7. A cofferdam glue, characterized in that: The invention comprises the following components in parts by weight: 5-15 parts of epoxy resin, 60-80 parts of filler, 10-15 parts of curing agent, 1-10 parts of curing accelerator, 1-5 parts of thixotropic agent and 0.5-3 parts of coupling agent; Wherein, the curing accelerator includes the curing accelerator as described in claim 1 or 2, and / or the curing accelerator prepared by the preparation method of the curing accelerator according to any one of claims 3-6.
8. The cofferdam glue according to claim 7, characterized in that: The epoxy resin comprises at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, naphthalene epoxy resin, aminophenol epoxy resin, aliphatic epoxy resin and biphenyl epoxy resin; and / or, the molecular weight of the epoxy resin is less than or equal to 600; And / or, the filler comprises spherical silica, the particle size of the spherical silica is distributed in the range of 1 μm-100 μm, and the average particle size is 5 μm-20 μm; And / or, the curing agent includes at least one of an amine curing agent and an acid anhydride curing agent; And / or, the coupling agent includes at least one of an epoxy coupling agent, an amino coupling agent, an aniline coupling agent, a mercapto coupling agent and a vinyl coupling agent; And / or, the thixotropic agent includes at least one of fumed silica, organic bentonite and hydrogenated castor oil.
9. The cofferdam glue according to claim 8, characterized in that: The curing agent includes an anhydride curing agent, and the molecular weight of the anhydride curing agent is less than or equal to 500.
10. Use of the dam glue according to any one of claims 7 to 9 in electronic device packaging.
Citation Information
Patent Citations
Microencapsulated silane coupling agent
CN101952364A
Imidazolyl polysilsesquioxane adsorbent material, and preparation method and application thereof
CN103193980A
Imidazolyl group modified silicone oil, and preparation method and application thereof
CN103396551A
Preparation method of terminal alkoxy polysiloxane
CN103467745A
Ionic liquid bonded polysiloxane stationary phase and preparation method thereof
CN103736469A